A study of nitrogen and boron impacts on yield and significance of cotton (Gossypium hirsutum L.) - Rikhtegar S. Hossein; Mohammad Eskandari; Hossein Rezaei (African Journal of Environmental Economics and Management, 2014)
This study was carried out to determine nitrogen (N) and boron (B) effects on yield and quality of cotton (Gossypium hirsutum L.). N was applied to the soil at rates of 0, 100, 200 and 300 kg ha-1 and B was applied as foliar at rates 0, 500 and 1000 g ha-1. Statistical results of study showed that N application significantly (P ≤ 0.05) increased boll number, boll weight, seed cotton weight of boll, seed cotton yield and lint yield. Moreover, leaf blade N concentration was affected by N application rate and increased significantly. Results of study also showed that the highest seed cotton yield was obtained in case of 200 kg ha-1 N application rate, and this application rate resulted in 19.6% increased seed cotton yield. Statistical results also indicated that foliar application of B significantly increased boll number, boll weight, seed cotton yield and lint yield. In addition, leaf blade B concentration was affected by B application rate and increased significantly. Results also demonstrated that the highest seed cotton yield was recorded in case of 1000 g ha-1 foliar application of B, and this foliar application rate resulted in 25% increased seed cotton yield. Statistical results showed that effect of different application rates of N was not significant for all fiber properties (fiber length, fiber strength and fiber fineness). Conversely, results of study indicated that different application rates of B significantly affected some fiber properties. On the whole, application of 200 kg ha-1 N and 1000 g ha-1 B (two time foliar B application) resulted in the highest boll number, boll weight, seed cotton yield and lint yield, and enhanced fiber properties. The interaction of N × B was not significant for all studied traits.